There and back again : J R R Tolkien and the origins of the Hobbit - Atherton, Mark (I.B. Tauris, 2012)
Mark Atherton here explores the chief influences on Tolkien's work: his boyhood in the West Midlands; the landscapes and seascapes which shaped his mythologies; his experiences in World War I; his interest in Scandinavian myth; his friendships, especially with the other Oxford-based Inklings; and the relevance of his themes, especially ecological themes, to the present-day. "There and Back Again" offers a unique guide to the varied inspirations behind Tolkien's life and work, and sheds new light on how a legend is born.